Sekolah Progresif - Syamsul Kurniawan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
As we know MEA has created competitive situation that means school must be able to answer market needs of workers. School must produces a good quality of education student that be able to compete in the global market. It means scholl must be reincarnated into progressive school. Discourse of progressive school has created by the writer based on john dewey originally ideas of progressivism.